Birds along a transect across KwaZulu-Natal: altitudinal preference and altitudinal migration - Scott, Tanya (Animal Demography Unit (ADU), 2018)
The special ornithological advantage of KwaZulu-Natal is the massive altitudinal gradient between the coastline and the Drakensberg Mountains, an altitudinal range in excess of 3000 m. It is one of the best places in the world to study altitudinal bird migration. This dissertation uses the bird data from the Second Southern African Bird Atlas Project (SABAP2), and altitudinal data from a Digital Elevation Model to try to understand altitudinal migration in a band of KwaZulu-Natal between 29°S and 30°S. The bird atlas provides data on a five minute grid, grid cells with sides of c. 9km, known as pentads. The Digital Elevation Model gives spot heights at 0.5 minute intervals. It therefore provides 100 altitudes in each pentad. There is a description of the data analysis approach used to relate bird species abundance to altitude and selected examples to show how the method works, illustrating the strengths and weakness of the approach. The developed method is then applied to the study area to investigate altitudinal migration. For each of the 304 species which occur with some regularity in the study area, the altitudinal height preferences in summer and winter are plotted and compared. Some species, such as African Dusky Flycatcher, are definite altitudinal migrants, and some species are definite residents having essentially identical altitudinal distributions in summer and winter, such as Black-bellied Starling. There are also many intermediate strategies. Numerous species have been proposed as altitudinal migrants in KwaZulu-Natal. These claims are evaluated against the results obtains in this dissertation. For some species, the suggestion that they are altitudinal migrants is clearly incorrect, and for other species the hypotheses are confirmed by the bird atlas data. The project attempted to determine if there were common factors that helped explain which species engaged in altitudinal migration. A set of life history characteristics for each species, including aspects such as diet, mass, habitat, etc, was used to evaluate if there was a relationship between the extent of altitudinal migration and these explanatory variables. No meaningful relationships were found. Explanations of altitudinal migrations therefore remain an enigma.